New Interpolation Functions in Eigen-Frequency Analysis of Timoshenko Beams on Two-Parameter Elastic Soil - Bruno, M. C.; Di Capua, V.; Franciosi, C. (Engineering Transactions, 1996)
The aim of the paper is to study the dynamic behaviour, limited to the eigen-value problem, of Timoshenko beams on variable two-parameter elastic soil. The analysis is performed by means of two different finite elements, with cubic and quintic interpolation laws, the mass and stiffness matrices are analytically calculated, and their performances are briefly discussed. Some numerical examples end the paper, in which the good convergence rate of the elements is shown, and a comparison is made with a powerful Rayleigh-Ritz approximation.